2021
DOI: 10.1101/2021.07.12.452013
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

In situ solid-liquid extraction enhances recovery of taxadiene from engineered S. cerevisiae cell factories

Abstract: A novel in situ solid phase adsorption strategy was investigated for enhanced recovery of taxadiene, a precursor to the blockbuster anticancer drug, paclitaxel, from engineered Saccharomyces cerevisiae. A synthetic adsorbent resin (HP-20) was employed to capture taxadiene across a range of cultivation scales. Cultivations from 12 % (w/v) resin concentration resulted in bead fragmentation which were found to be detrimental to cellular growth. After cultivation, the use of acetone for desorption captured intrace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…This suggested that the integration of additional genes resulted in a decreased cellular fitness. In addition, the LRS5 strain was recently found to have a reduced mechanical stress tolerance compared to the wild-type, CEN.PK-1C, strain [40]. In the presence of an in situ solid phase adsorbent resin with a concentration of 12% w/v, the growth of LRS5 was completely inhibited, whilst the growth of the parental CEN.PK-1C was not significantly affected, further suggesting that metabolic engineering has a detrimental effect on cellular fitness and stress tolerance.…”
Section: Quorum Sensing In S Cerevisiaementioning
confidence: 99%
“…This suggested that the integration of additional genes resulted in a decreased cellular fitness. In addition, the LRS5 strain was recently found to have a reduced mechanical stress tolerance compared to the wild-type, CEN.PK-1C, strain [40]. In the presence of an in situ solid phase adsorbent resin with a concentration of 12% w/v, the growth of LRS5 was completely inhibited, whilst the growth of the parental CEN.PK-1C was not significantly affected, further suggesting that metabolic engineering has a detrimental effect on cellular fitness and stress tolerance.…”
Section: Quorum Sensing In S Cerevisiaementioning
confidence: 99%